Islamic Worldview dan Urgensinya - Rika Sartika; Habibah, Alif Rohmah Nur (Adabuna : Jurnal Pemikiran dan Pendidikan, 2022)
This article seeks to describe Islam as a worldview as a driving force for change for Muslims, not just a religion that pays attention to creed and ritual issues. As a worldview, Islam has an integrated view of physical and non-physical reality. The method used in this article is an explanatory qualitative method with a generative approach that identifies in detail the urgency of the Islamic Worldview. This article uses an analysis of literature studies by comparing and reviewing several literature such as textbooks, scientific journals, and others related to the Islamic Worldview. The result of this paper is that Islam as a worldview is closely related conceptually to all human activities as social, intellectual, and religious beings which makes faith in God very important and the most important element. The first key is faith, the purity of knowledge from the Qur'an and the transformation of scientific customs then channeled with the senses as well as common sense.